Deep red upconversion photoluminescence in Er3+‐doped Yb3Ga5O12 nanocrystalline garnet. Issue 5 (14th January 2022) - Netolicky, Tomas; Strizik, Lukas; Benes, Ludvik; Melanova, Klara; Slang, Stanislav; Wagner, Tomas
Abstract: The nanocrystalline single‐phase Er 3+ ‐doped Yb3 Ga5 O12 garnets have been prepared by the sol‐gel combustion technique with a crystallite size of ≈30 nm. The presence of Yb 3+ in garnet hosts allows their efficient excitation at the ≈977 nm wavelength. The Er 3+ doping of Yb3 Ga5 O12 garnet host results in deep red Er 3+ : 4 F 9/2 → 4 I 15/2 upconversion photoluminescence (UCPL) emission. The dominance of the red UCPL emission over the green Er 3+ : 4 F 7/2 / 2 H 11/2 / 4 S 3/2 → 4 I 15/2 component was investigated using the measurement of the steady‐state and time‐dependent Er 3+ and Yb 3+ emission spectra in combination with the power‐dependent UCPL emission intensity. The proposed upconversion mechanism is discussed in terms of the Er 3+ → Yb 3+ energy back transfer process as well as Yb 3+ (Er 3+ ) → Er 3+ energy transfer and Er 3+ ↔ Er 3+ cross‐relaxation processes. The studied Er 3+ ‐doped Yb3 Ga5 O12 garnet may be utilized as a red upconversion emitting phosphor.